Implementasi Perbandingan Metode Algoritma Support Vector Machine (SVM) DAN Naïve Bayes Untuk Menganalisa Pendapat Masyarakat Terkait Cyberbullying Diera Teknologi Digital Pada Aplikasi X - Awaludin, Ibnu; Zakaria, Hadi (CV. Shofanah Media Berkah, 2024)
In the era of digital technology, technological advances have changed the way people interact, but have also increased cases of cyberbullying, especially among children and adolescents who use the X application. Cyberbullying perpetrators feel safe from direct consequences because of the anonymity of the internet. The Indonesian Psychological Practice Foundation (YAPI) is concerned about this problem and plans to develop an application to analyze public opinion about cyberbullying on social media X. This study aims to analyze public opinion using the Support Vector Machine (SVM) and Naïve Bayes Algorithms, and identify the most efficient and accurate methods in terms of speed and accuracy. Data from the X platform will be taken using Python, processed through preprocessing, and stored in a MySQL database. This study is expected to determine the superior method between SVM and Naïve Bayes, as well as provide a better understanding of preprocessing techniques in analyzing opinions on social media, thereby improving the quality and relevance of the analysis results.